EVALUATING COMMUNICATION SKILLS TRAINING FOR NEWLY GRADUATED NURSING TECHNICIANS IN SAUDI ARABIAN HOSPITALS: A CROSS-SECTIONAL STUDY - Adnan Fawaz Alharbi, Fahad Mudhi Khalif Al-Anzi, Sarah Hamoud Alshammari, Fatima Hussein Saadoun Alnasafi, Norah Mudhi Khulaif Alanazi, Dalal Mudhi Khalif Al-Anazi, (Chelonian Research Foundation, 2022)
Effective communication is vital for newly graduated nursing technicians to deliver quality care, yet preparation gaps exist. This cross-sectional study evaluated perspectives on prior communication skills training among 175 new Saudi nursing technicians. Surveys assessed training quantity, topics, modalities, perceived effectiveness, and recommendations. Results showed limited training with deficits in simulation practice, culture competency, and empathy development. Significant positive correlations emerged between training satisfaction and communication self-efficacy. Participants emphasized needs for expanded curricula, experiential modalities, and ongoing reinforcement. Ensuring comprehensive communication content, competency-building modalities, and continuity in training programs is imperative to strengthen nursing communication capabilities.